Primary Pelvic Involvement of Hydatid Disease - Tosun, Migraci; Durak, Yıldırım; Çelik, Handan; Bıldırcın, Devran; Çetinkaya, Mehmet Bilge; Yılmaz, Ali Faik (Gynecology Obstetrics & Reproductive Medicine, 2011)
Hydatid disease is caused by larval stage of a parasite named as Echinococcus. To diagnose this condition may be challenging without surgery and postoperative pathological examination due to limited value of serological studies but imaging techniques may give a clue when hydatid disease is suspected and hydatid disease shall be considered for differential diagnosis in pelvic mass. In the present case, we present a 75-year-old postmenopausal woman with pelvic hydatosis.